2011
DOI: 10.1111/j.1440-1754.2011.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body mass index and triceps skinfold at 5 years and young adult body mass index, waist circumference and blood pressure

Abstract: In children with overweight/obesity, BMI rather than triceps skinfold is the preferred epidemiological measure for identifying young adult CVD risk markers of BMI, WC and blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…These results reflect those of the meta-analysis for older age ranges, although they might suggest that diagnosis of obesity at age 5 years does not track to adult obesity. The findings from the study by Liddle et al (2012) 127 on the predictive ability of triceps SFT reflect those for BMI, except that the sensitivity and specificity results are slightly poorer. This study does not provide evidence that SFT might be a better measure in children than BMI.…”
Section: Additional Information From Studies That Could Not Be Includmentioning
confidence: 79%
See 2 more Smart Citations
“…These results reflect those of the meta-analysis for older age ranges, although they might suggest that diagnosis of obesity at age 5 years does not track to adult obesity. The findings from the study by Liddle et al (2012) 127 on the predictive ability of triceps SFT reflect those for BMI, except that the sensitivity and specificity results are slightly poorer. This study does not provide evidence that SFT might be a better measure in children than BMI.…”
Section: Additional Information From Studies That Could Not Be Includmentioning
confidence: 79%
“…numbers of true and false positives, and true and false negatives) were included in the meta-analyses, except for the study by Liddle et al (2012), 127,128 which was of children aged 5 years only and therefore did not fall into the lowest age category of the meta-analysis (7-11 years); the results of this study are presented in the previous section. Different studies reported data on different comparisons between childhood and adult obesity or overweight, and at different ages.…”
Section: Meta-analysis Of Tracking Of Obesity Into Adulthoodmentioning
confidence: 99%
See 1 more Smart Citation
“…The year that each study started varied considerably, ranging from 1923 to 1989 while the year that studies were published ranged from 1971 to 2014. Studies were conducted in eleven different countries; six in the U.S. [ 4 , 64 , 66 , 67 , 73 , 75 ], three in United Kingdom (England, Wales, Scotland and Newcastle) [ 76 , 83 , 85 ], three in Finland [ 65 , 68 , 81 ], two in Australia [ 77 , 82 ], and one in either Sweden [ 69 ], India [ 71 ], Lithuania [ 72 ], Poland [ 74 ], the Republic of Seychelles [ 78 ], Japan [ 79 ], or the Solomon Islands [ 84 ]. Most studies used a prospective longitudinal study design except for two studies that used a retrospective study design [ 65 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have previously found BMI in preschool ages to be linked to adult waist circumference [24], [25] and BMI change from 2 to 6 years has been linked to metabolic alterations (blood pressure, HDL and triglycerides) in adulthood [14]. Fall et al failed to detect significant linear associations between simple childhood BMI measures before the age of 5 years and individual metabolic measures in adulthood [24], but significant associations have been found at BMI rebound [15]and among older children [2], [24].…”
Section: Discussionmentioning
confidence: 91%